Women's Lived Landscapes of War and Liberation in Mozambique Bodily Memory and the Gendered Aesthetics of Belonging - Katto, Jonna (Taylor & Francis, 2019)
This book tells the history of the changing gendered landscapes of northern Mozambique from the perspective of women who fought in the armed struggle for national independence, diverting from the often-told narrative of women in nationalist wars that emphasizes a linear plot of liberation. Taking a novel approach in focusing on the body, senses, and landscape, Jonna Katto, through a study of the women ex-combatants' lived landscapes, shows how their life trajectories unfold as nonlinear spatial histories. This brings into focus the women's shifting and multilayered negotiations for personal space and belonging. This book explores the life memories of the now aging female ex-combatants in the province of Niassa in northern Mozambique, looking at how the female ex-combatants' experiences of living in these northern landscapes have shaped their sense of socio-spatial belonging and attachment. It builds on the premise that individual embodied memory cannot be separated from social memory; personal lives are culturally shaped. Thus, the book does not only tell the history of a small and rather unique group of women but also speaks about wider cultural histories of body-landscape relations in northern Mozambique and especially changes in those relations. Enriching our understanding of the gendered history of the liberation struggle in Mozambique and informing broader discussions on gender and nationalism, this book will be of interest to students and scholars of African history, especially the colonial and postcolonial history of Lusophone Africa, as well as gender/women's history and peace and conflict studies.